STRUKTUR KOMUNITAS BINTANG LAUT PADA EKOSISTEM TERUMBU KARANG DI PERAIRAN TIHI-TIHI KOTA BONTANG - Ana Yumi; Dewi Embong Bulan; Irma Suryana (Jurnal Tropical Aquatic Sciences, 2022)
Star fish has been interested to study over the seas of east Kalimantan. This study was conducted in April to May 2019 in the coral reefs ecosystem at the waters of Tihi-Tihi Bontang. This study was aimed to determine the types of starfish, diversity index, uniformity index and dominance index. The stations were consisted in three location by using transect direct survey in line of 70 m which range of width to 10 m in area of coral reefs, it was collected picture of starfish detail in natural life and continued to identify in land without take out the object from habitat. Data was analyzed using index from Odum. The result was showed two types of species confirmed in each station. In general, the diversity index was concluded in low range, the uniformity index in range of 0.40 to 0,75 and dominance of Protoreaster nodosus was confirmed at station 3, which 14 times then Linckia laevigatathe.